THE IMPACT OF LEAN INITIATIVES ON EMPLOYEE’S SATISFACTION: THE CASE STUDY OF A PILOT PROJECT IN A SERVICE COMPANY - Martins, A.; Morgadinho, A.R. (International symposium on logistics 2015 - Reflections on supply chain research and practice, 2015)
When lean is applied in services benefits rapidly emerge if employees are committed. Organizations examine conditions that foster greater employee satisfaction, because satisfied employees make positive contributions to organizational effectiveness and performance. This paper aims at analysing if lean initiatives from a pilot project in a bank had any impact on employees’ satisfaction at work and which adjustments are required to expand the pilot. Findings show that although employees state that they have Lean Understanding and a positive perception of new Job Characteristics, they tend to go back to old practices. This shows lack of both employee engagement and reinforcement from the leading Training Team. Lack of reinforcement led to a poor employees’ perception of Lean Success. Although Lean initiatives have had a positive impact on employees’ satisfaction at work, they perceive higher level of Autonomy, Leadership and Work Facilitation when Management Commitment is high and Lean Tools are used more.